Penerapan Asas Restitutio In Integrum Terhadap Pinjaman Online Ilegal Yang Merugikan Masyarakat - Aditya Wisnu; Kukuh Tejomurti (Journal of Law, Society, and Islamic Civilization, 2026)
Peer-to-peer lending are one of the fintech services that can affect the stability of the financial system in Indonesia. However, it is ironic that the number of legal peer-to-peer lending lags far behind the number of illegal ones circulating in society. Illegal peer-to-peer lending causes the society to suffer various losses, such as reduced or lost assets due to high interest rates, disruption of personal life due to violations of privacy rights, and damage to the sense of security and protection due to threatening collection practices. According to the principle of restitutio in integrum, a person who suffers losses due to unlawful acts is entitled to restoration of the situation to its original state prior to the violation. In this case, the affected society is entitled to compensation for losses incurred due to illegal peer-to-peer lending activities. Therefore, this study was conducted to determine the liability of illegal peer-to-peer lending for these losses, based on the principle of restitutio in integrum. The research method used to analyze the legal issues is normative/doctrinal legal research, which is prescriptive and applied. This approach uses a statutory and conceptual method based on literature, such as regulations, books, articles, and other sources related to legal issues. According to Djojodirdjo, four elements must be met for this principle to apply: unlawful act (onrechtmatige daad), fault (schuld), damage (schade), and causal connection (oorzakelijk verband). Based on the findings, illegal peer-to-peer lending that detrimental to society may be subject to the principle of restitutio in integrum. The public may sue for compensation for losses incurred due to illegal peer-to-peer lending, in the form of nominal, compensatory, or punitive damages.